Oral Manifestations of COVID-19: Updated Systematic Review With Meta-Analysis - Aragoneses, Javier; Suárez, Ana; Algar, Juan; Rodríguez, Cinthia; López-Valverde, Nansi; Aragoneses, Juan Manuel (Frontiers in Medicine, 2021)
There is increasing evidence for oral lesions and manifestations of COVID-19. The aim of this meta-analysis was to investigate the types of oral manifestations of COVID-19 and their prevalence. PubMed/Medline, Scopus, Web of Science, and Google Scholar databases were used to search for publications on oral manifestations in patients with PCR-confirmed COVID-19. A total of 310 records were selected, and 74 were included. Oral lesions in COVID-19 were classified according to their etiologies, including iatrogenic lesions caused by intubation and opportunistic infections. Of the included studies, 35 reported oral lesions probably caused by severe acute respiratory syndrome-Coronavirus-2 (SARS-CoV-2) infection. Meta-analysis of prevalence data on oral manifestations and aphthous lesions indicated high heterogeneity, while meta-analysis of xerostomia prevalence data revealed a pooled prevalence, with considerable heterogeneity. In conclusion, the meta-analysis yielded high heterogeneity between studies: oral lesions yielded a prevalence of 0.33 (95% CI 0.11–0.60), xerostomia lesions a prevalence of 0.44 (95% CI 0.36–0.52) and aphthous lesions 0.10 (95% CI 0.01–0.24). In addition, a gap in the evidence regarding the prevalence of oral lesions in COVID-19 was identified and the need for further observational studies focusing on this issue and on the causal relationships between oral lesions and COVID-19 was highlighted.